Evaluación de la implementación de un sistema de tubería flexible termoplástica en las líneas de transporte primarias y secundarias en el Campo Palagua (2020)
The document describes the characteristics of the pipeline proposed for the Field in order to choose the appropriate one for it. Subsequently, a simulation is carried out in the “PIPE sim 2017” software with the characteristics of the environment and soil of the field and, in turn, with the physicochemical characteristics of the proposed pipeline. Different simulations are carried out and parameters such as the length and location of the pipe are taken into account.